Survey of Student Interest in Volleyball Bottom Passing Learning at The Junior High School Level of North Musi Rawas Regency - Anis, Anis; Lanos, Muhsana El Cintami; Imansyah, Farizal (Journal of Social Work and Science Education, 2023)
Conventional learning and student-centered learning tend to affect students' interest in learning, especially in physical education learning material passing down techniques. This research is qualitative descriptive research with a type of survey research. The population of this study was 80 students. The sample of this study used a random sampling technique so the number of samples in this study was 40 people. Respondents in this study as many as 40 students, the conclusion of this study is that more interactive and fun learning through games for the level of effectiveness of learning basic passing techniques under basketball is in the good category. The purpose of this study aims to determine the level of student interest in learning basic passing techniques under volleyball at the junior high school level of North Musi Rasawa Regency.